(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Non-thyroidal illness is prevalent in patients with advanced stages of chronic kidney disease and could be considered as a risk factor for cardiovascular mortality; this relation is partially explained by malnutrition and the concomitant condition of high inflammation. This study is designed to investigate the relationship between left ventricular mass and thyroid hormone abnormalities and evaluate this relationship after adjustment of inflammatory factors and nutritional status in peritoneal dialysis patients. Methods. A total of 71 patients undergoing maintenance peritoneal dialysis were included. Serum concentration of total and free triiodothyronine (fT3), total and free thyroxine (fT4), and TSH were measured. LV mass index and the structural properties of heart including LVEDD, LVESD, PWD, and EF were assessed by transthoracic echocardiography. The Surrogates of Inflammation, including IL-6, albumin, and hs-CRP were measured. The nutritional status of patients was assessed by one point SGA scoring and biochemical data. The relation between thyroid hormones and echocardiographic variables, inflammatory and nutritional markers was determined. Results. LVMI was significantly higher in the group with lower fT3 levels. Linear regression analyses showed statistically significant univariate association between fT3, tT3, and tT4; and LVMI. In multiple linear regression analysis adjusted for albumin, hs-CRP, IL- 6, and ferritin; only fT3 level had a meaningful negative correlation (P < .05) with LVMI, free T3 level was positively correlated with rGFR (P < .05, c = 0.39) and KT/V (P < .05, c = 0.27). Conclusion. Low fT3 level was negatively and significantly associated with LVML even after adjustments for known risk factors in peritoneal dialysis patients.